Pengaruh Karakteristik Dewan, Kualitas Audit, dan Narsisme Direktur Utama terhadap Penghindaran Pajak - Indah Rahayu; Ickhsanto Wahyudi (Owner : Riset dan Jurnal Akuntansi, 2025)
Taxes, as the main source of state revenue, are often perceived by companies as a high corporate expense, prompting them to engage in tax avoidance practices. This study aims to examine the influence of board independence, board gender diversity, board size, audit quality, and CEO narcissism on tax avoidance, with firm age, leverage (DAR), and profitability (ROA) as control variables. In this study, tax avoidance is measured by the effective tax rate (ETR), with a lower ETR indicating a higher level of tax avoidance activity. The research obtains data from the financial statements and annual reports of processed food industry companies over three periods, from 2021 to 2023, which are published on the Indonesia Stock Exchange website or the official websites of the studied companies. This research employs a quantitative approach with secondary data. The sample consists of 48 observations over 3 research periods and 16 processed food industry companies in Indonesia, selected through purposive sampling. The results of this study indicate that board independence, board size, audit quality, and CEO narcissism do not have an effect on tax avoidance, whereas board gender diversity has a negative effect on tax avoidance in the processed food industry. These findings highlight the importance for companies to consider the inclusion of women on the board of directors as a strategy to enhance corporate governance. The presence of women on the board reflects a higher ethical culture, more transparent practices, stronger compliance, and a tendency to reduce corporate tax avoidance.